Chemical and Technological Properties of European Cranberrybush (Viburnum opulus L.) Fruits - AKBULUT, MEHMET; CALISIR, SEDAT; MARAKOGLU, TAMER; COKLAR, HACER (Asian Journal of Chemistry, 2010)
The European cranberrybush (Viburnum opulus L.) fruits were analyzed for selected technological properties (dimensions, geometric mean diameter, sphericity, bulk density, fruit density, volume, terminal velocity, rupture strength, porosity) and proximate composition (moisture, reducing sugar, ascorbic acid, total anthocyanin and phenolics, crude protein, crude oil, crude energy, crude fiber, ash, pH, acidity, alcohol soluble extract and colour) properties. Mineral content of Viburnum opulus growing in Turkey were determined by inductively coupled plasma atomic emission spectrometer (ICP-AES). All materials contained high amounts of Ca, K, Mg, Na, P and S. The average pulp mass ratio, thickness, width, length, mass, volume, geometric mean diameter, sphericity and projected area were measured as 653.0 g/kg, 9.59 mm, 9.71 mm, 10.18 mm, 0.65 g, 638 mm3, 9.82 mm, 0.96 and 0.9988 cm2, respectively. The energy, reducing sugar, protein, cellulose, oil, ash, acidity, ascorbic acid, total phenolics, total anthocyanin and soluble solid matter values of European cranberrybush fruits were established as 256.56 kJ/g, 63.46 g/kg, 64.85 mg/kg, 180.71 g/kg, 6.70 g/kg, 12.83 g/kg, 17.92 g/kg, 595.24 mg/kg, 3253.87 mg/kg, 654.23 mg/kg and 104.31 g/kg, respectively. It is very important to evaluate the technological properties of equipment used harvesting, transportation, storage and processing of fresh fruits. Also, the information supplied on the chemical properties of the European cranberrybush fruit serves as food in human nutrition.